Impact of cysteine variants on the structure, activity, and stability of recombinant human α‐galactosidase A. (14th July 2015) - Qiu, Huawei; Honey, Denise M.; Kingsbury, Jonathan S.; Park, Anna; Boudanova, Ekaterina; Wei, Ronnie R.; Pan, Clark Q.; Edmunds, Tim
Abstract Recombinant human α‐galactosidase A (rhαGal) is a homodimeric glycoprotein deficient in Fabry disease, a lysosomal storage disorder. In this study, each cysteine residue in rhαGal was replaced with serine to understand the role each cysteine plays in the enzyme structure, function, and stability. Conditioned media from transfected HEK293 cells were assayed for rhαGal expression and enzymatic activity. Activity was only detected in the wild type control and in mutants substituting the free cysteine residues (C90S, C174S, and the C90S/C174S). Cysteine‐to‐serine substitutions at the other sites lead to the loss of expression and/or activity, consistent with their involvement in the disulfide bonds found in the crystal structure. Purification and further characterization confirmed that the C90S, C174S, and the C90S/C174S mutants are enzymatically active, structurally intact and thermodynamically stable as measured by circular dichroism and thermal denaturation. The purified inactive C142S mutant appeared to have lost part of its alpha‐helix secondary structure and had a lower apparent melting temperature. Saturation mutagenesis study on Cys90 and Cys174 resulted in partial loss of activity for Cys174 mutants but multiple mutants at Cys90 with up to 87% higher enzymatic activity (C90T) compared to wild type, suggesting that the two free cysteines play differential roles and that the activity of the enzyme can be modulated by side chain interactions of the free Cys residues. These results enhanced our understanding of rhαGal structure and function, particularly the critical roles that cysteines play in structure, stability, and enzymatic activity.